Urgensi Sektor UMKM Persaingan Usaha Sebagai Penyangga Ibu Kota Negara Nusantara - Pribadi, Deny Slamet; Nur, Insan Tajali; Wardhana, Kristiawan Wisnu (Fakultas Syariah INSURI Ponorogo, 2023)
The MSME sector is indeed a big challenge in ensuring the continuity of entrepreneurship. This entrepreneurial interest is still not accompanied by commensurate capacity in running a business. The purpose of this study is to examine and analyze the Micro, Small and Medium Enterprises (MSMEs) sector in the National Capital Region (IKN) and collaboration and local authorities for business activists. The research method used in this research is empirical juridical. The primary data source uses Law Number 80 of 2008 concerning Micro, Small and Medium Enterprises. The data collection used by researchers is by using certain research methods that are adapted, namely by way of question and answer, observation and documentation to collect as much data as possible. Data analysis technique; condensing data and drawing conclusions. The results of the study concluded that this sector is able to meet the needs of clothing and food. Regulators should accommodate the progress of MSME businesses. The existence of IKN has the potential to increase people's welfare. The weaknesses are the degradation of the area and the income of the community's economic value and local authorities.